Regulation of the Institute of Conditional Release in Lithuania: Development and Application Challenges - Norvaišytė, Goda (Teisė, 2025)
Since May 1, 2003, when the Penal Code of the Republic of Lithuania came into force, the regulation of conditional release in Lithuania has changed several times. The conditions initially depended on disciplinary categories: less serious cases required serving half of the sentence, while recidivists had to serve up to three-quarters. There were exceptions as well – since, for example, pregnant women or parents with minor children could be released after serving one-third of their sentence. Later amendments introduced additional criteria, such as behavior, incentives, and disciplinary sanctions. A significant change occurred in 2012, when the Law on Probation of the Republic of Lithuania came into effect, and Conditional Release Commissions were established. Although recent statistics indicate a more effective application of conditional release, a deeper analysis reveals persistent issues, among which, particularly, an overestimation of prisoner risk levels and the lack of synergy between the Conditional Release Commissions and the courts. Conditional release is an important tool for social reintegration, helping convicted persons gradually reintegrate into society. It promotes public safety, reduces crime, and mitigates the harmful effects of imprisonment. It is considered a component of progressive sentence enforcement, ensuring a structured transition from incarceration to life in freedom through individualized conditions and supervision. Lithuanian statistics from 2020 to 2024 show that this measure is effective as the proportion of individuals who successfully completed conditional release increased from 68% (in 2020) to 81% (in 2024).
Keywords: conditional release from imprisonment; resocialization; custodial sentence